Phytochemical Profiling and Analytical Standardization of Saraladi Yoga: An Ayurvedic Vaginal Fumigation Formulation - Dr. Asha K P,; Prof. Manjusha Karkare,; Dr. Saurabh Agrawal, (The Bioscan, 2025)
Background: Saraladi Yoga, a classical Ayurvedic formulation documented by Acharya Charaka, represents a sophisticated therapeutic approach for managing abnormal vaginal symptoms (Yonigata Lakshanas) through Yoni Dhupana (vaginal fumigation). Objective: This study integrates a systematic appraisal with comprehensive analytical validation including HPTLC fingerprinting to establish scientific credentials for this traditional formulation. Methods: The formulation comprising Sarala (Pinus longifolia), Guggulu (Commiphora mukul), Yava (Hordeum vulgare), and Ghrita (ghee) was subjected to organoleptic evaluation, physicochemical analysis, phytochemical screening, and HPTLC fingerprinting at a Ministry of AYUSH approved laboratory. Classical literature was systematically reviewed alongside modern research on individual components. Results: Physicochemical analysis revealed optimal moisture content (0.47%), high extractive values (water-soluble: 23.98%, alcohol-soluble: 25.84%), appropriate pH (5.07), and rich phytochemical profile with significant presence of tannins (+++), flavonoids (++), and saponins (++). HPTLC fingerprinting detected 18 unique compounds across three detection wavelengths (254nm, 366nm, 540nm), with characteristic Rf values providing a comprehensive chemical signature. Conclusion: The integrated analytical findings strongly correlate with the formulation's traditional therapeutic applications, establishing a robust scientific foundation for its antimicrobial, anti-inflammatory, and tissue-healing properties through localized fumigation therapy.